Creditworthiness Assessment for Credit Institutions and for the Risk Associated with Excessive Leverage toward Sustainable Performance - Razvan Sorin Șerbu (MDPI AG, 2021)
With the development of financial transactions, it has become necessary for parties to assess the creditworthiness of their counterparty before entering into an agreement. In this respect, z-scoring methods for assessing creditworthiness have been developed, credit risks have been regulated, and rating providers have emerged to ensure a certain level of independence. This article introduces a z-scoring methodology, developed using principal component analysis, for assessing the creditworthiness of credit institutions; a methodology for determining the rating corresponding to the scoring obtained by the entities, developed through expert judgement; and an analysis of the existence of a significant correlation between z-scoring and the level of the leverage and capital adequacy ratios. Furthermore, considering that excessive leverage can have a negative impact on the creditworthiness of an entity, a methodology for assessing the leverage ratio is presented, along with a method for determining any additional own fund requirements where this ratio is above the regulated maximum level. The results obtained by applying the described methodologies to the data of the entities showed stable character. All these methodologies can be implemented by credit institutions to achieve better creditworthiness and business sustainability.